Pengaruh Motivasi Kerja dan Disiplin terhadap Kinerja Pegawai Rumah Sakit: Literatur Review - Sihombing , Veronika Dinar Romauli (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Employee performance is a critical determinant of service quality and organizational effectiveness in hospital management. High levels of work motivation and work discipline are essential factors that influence employees’ commitment, productivity, and quality of healthcare services. This study aims to analyze and synthesize empirical evidence regarding the effect of work motivation and work discipline on hospital employee performance through a systematic literature review. Relevant articles were identified from reputable scientific databases, including Google Scholar, PubMed, ScienceDirect, Scopus, and Garuda, published between 2015 and 2024. The selection process applied inclusion and exclusion criteria to ensure the relevance, credibility, and quality of the reviewed studies. Data were analyzed using thematic synthesis and descriptive-analytical approaches to identify patterns, relationships, and research trends. The findings indicate that work motivation significantly influences employee performance by enhancing job satisfaction, commitment, and engagement. Work discipline also plays a crucial role in improving adherence to operational standards, punctuality, and service efficiency, which directly affect service quality and patient safety. Moreover, the interaction between work motivation and work discipline demonstrates a synergistic effect, leading to optimal and sustainable employee performance. Supporting factors such as transformational leadership, conducive work environment, fair compensation systems, organizational culture, and effective performance management further strengthen this relationship. In conclusion, strengthening work motivation and work discipline through integrated human resource management strategies is essential to improving hospital employee performance and service quality. These findings provide valuable insights for hospital managers and policymakers in designing evidence-based interventions to enhance organizational effectiveness and healthcare service outcomes.